2020
DOI: 10.1002/adtp.202000078
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing Inactive Conformations of MALT1 as an Effective Approach to Inhibit Its Protease Activity

Abstract: The paracaspase MALT1 (mucosa associated lymphoid tissue lymphoma translocated gene 1) plays an important role in various immune pathways and is proposed as a therapeutic target for autoimmune disorders as well as different types of cancer, such as diffuse large B‐cell lymphoma (DLBCL). Different mechanisms are explored to inhibit the protease activity of MALT1 and two unrelated chemical scaffolds are discovered. Biophysical and structural studies reveal that both scaffolds stabilize the protease in an inactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Expression and purification of MALT1 Casp1‑Ig3 for crystallization and biophysical studies have been described. , MALT1(329–728) at 12 mg/mL, in 25 mM HEPES pH7.5, 50 mM NaCl, and 1 mM TCEP, was mixed with TC1 in 100% DMSO at a final concentration of 0.5 mM. TCEP (10 mM) and MgCl 2 (10 mM) were added to the protein before setup.…”
Section: Methodsmentioning
confidence: 99%
“…Expression and purification of MALT1 Casp1‑Ig3 for crystallization and biophysical studies have been described. , MALT1(329–728) at 12 mg/mL, in 25 mM HEPES pH7.5, 50 mM NaCl, and 1 mM TCEP, was mixed with TC1 in 100% DMSO at a final concentration of 0.5 mM. TCEP (10 mM) and MgCl 2 (10 mM) were added to the protein before setup.…”
Section: Methodsmentioning
confidence: 99%
“…To explore the possible binding mode of lesbicoumestan to MALT1, we obtained the crystal structure of MALT1 as a template (3UO8) [ 16 ] from the Protein Data Bank [ 17 , 18 ] and a docking study was conducted to rationalize the inhibitory activity of lesbicoumestan using Autodock4 [ 19 ]. For binding pocket estimation, we selected the pocket in which the origin ligand posed, which was previously reported as a known paracaspase domain of MALT1 [ 16 , 20 ]. By comparing lesbicoumestan to the reported MALT1 inhibitor β-lapachone, we found that both were structurally similar molecules and had a partially closed scaffold.…”
Section: Resultsmentioning
confidence: 99%